EL ARBITRAJE EN EL ANTEPROYECTO DE CÓDIGO MERCANTIL - MANUEL OLIVENCIA RUIZ (Revista Internacional de Doctrina y Jurisprudencia, 2014)
On 30 May, it was approved by the Cabinet the Draft Commercial Code (ACM). The CGC Section 2 addresses the issue of corporate arbitration, this work wants to analyze.